Підвищення енергоефективності диспергування в пульсаційному гомогенізаторі рідких продуктів - Кюрчев, Сергій Володимирович; Самойчук, Кирило Олегович; Ковальов, Олександр Олександрович; Паляничка, Надія Олександрівна; В’юник, Ольга Володимирівна; Kiurchev, Serhii; Samoichuk, Kyryl; Kovalov, Oleksandr; Palianychka, Nadiia; Viunyk, Olha (Запоріжжя : ТДАТУ, 2024)
UA: В статті наведено аналізу пристроїв аналогу та прототипу корисної моделі, результати якого свідчать про конструктивні особливості, з врахуванням яких розглянуті конструкції не забезпечують необхідну якість диспергування в крайніх положеннях амплітуди руху поршня-ударника. Розглянуті конструкції відрізняються високими значеннями енерговитрат, пов'язаними з високими значеннями гідравлічного опору в середній частині амплітуди руху поршня-ударника. Запропоновано корисну модель, в якій обґрунтовано доцільність монтажу в отворах поршня-ударнику еластичних вставок, які мають наскрізні отвори. Обґрунтовано, що в крайніх положеннях амплітуди руху поршня-ударнику впровадження пропозиції забезпечить підвищення якості гомогенізації, а в середній частині амплітуди руху поршня дозволить досягти зниження енерговитрат при високій якості гомогенізації. EN: The decrease in the potential of energy producing companies in Ukraine associated with the terrorist actions of the aggressor country forces scientists and specialists in the food and processing industries to look for ways to increase the energy efficiency of industry processes. Homogenization is a normative process in the production of most dairy products. At the same time, dispersion for the most common valve homogenizers in industry has energy costs comparable to grain crushing processes. The results of promising studies allow us to say that it is possible to achieve a 5-6-fold reduction in specific energy costs for dispersion by studying and implementing designs based on the intense impact of impulses generated as a result of the reciprocating movement of the piston-impactor. The article analyzed the designs of the analogue and the prototype of the utility model. The results obtained allow us to assert that the considered designs cannot provide high quality homogeization when the piston-impactor approaches the top and bottom dead centers. In addition, the considered designs have high energy costs for dispersion in the middle part of the amplitude of movement of the piston-impactor, which is associated with large values of hydraulic resistance when liquid products pass through the holes in the piston-impactor. In the proposed utility model, it is recommended to install inserts made of elastic material that have through holes into the holes of the piston-impactor. The results of analytical studies indicate that such a measure will help improve the quality of homogenization at the extreme points of the amplitude of piston movement. On the other hand, the proposed measure makes it possible to reduce the energy costs for dispersion in the middle part of the amplitude of movement of the piston-impactor. The proposed measure avoids obliteration, increases the reliability of the design, ensuring the production of high quality products while simultaneously reducing the energy costs of the process.
Increasing the energy efficiency of dispersing in a pulsation liquid products homogenizer
Keywords: поршень-ударник; наскрізні отвори; шток; еластичні вставки; гомогенізована емульсія; диспергування; impactor piston; through holes; rod; elastic inserts; homogenized emulsion; dispersion